Validation of the Maternal Identity Scale for Primiparous Thai Teenage Mothers - Suphawadee Panthumas; Wirin Kittipichai (Elsevier, 2019)
Purpose: The Maternal Role Attainment Scale Form B (MRAS-Form B) was developed based on Mercer's theory and widely used to assess maternal role attainment among Thai mothers in hospitals. To assess the maternal identity among primiparous adolescent mothers in communities, MRAS-Form B remains indistinguishable due to differences in both mothers' ages and circumstances and was modified to the Maternal Identity Scale (MIS). Therefore, the aim of this study was to examine the validity and reliability of the MIS. Methods: A cross-sectional study was conducted among 397 primiparous Thai teenagers residing with their infants aged 4-12 months. Data were collected using self-administered questionnaires. Confirmatory factor analysis was performed to confirm the construct validity using Mplus Software. Results: The overall model provided fit well to the empirical data (χ2/df = 2.23, comparative fit index = .93, Tucker-Lewis index = .92, root mean square error of approximation = .06, standardized root mean square residual = .05). About 33-66% of the variance among MIS items could be explained by three constructs of maternal identity. Convergent validity showed item loadings ranging from .58 to .81; in addition, average variance extracted and composite reliability ranged from .44 to .54 and .82 to .92, respectively. Discriminant validity correlations between constructs were ranging from .74 to .87. The MIS exhibited very good item discrimination values (.52 ≤ corrected item-total correlation ≤.70) and an excellent reliability (Cronbach's α = .95). Conclusion: Appropriately for community health nursing, the MIS was a valid and reliable tool, assessing maternal identity among primiparous teenage mothers one year after delivery. Keywords: adolescent, community health nursing, factor analysis, statistical, mothers, postpartum period